Frequency and Risk Factors of Pneumonia and Urinary Tract Infection during Hospitalization in Acute Stroke Patients. - Ahmad, Shahed; Rahman, Matiur; Hosen, Mostafa; Kalam, Abul; Shoab, Mohammed; Islam, Md Rafiqul (Bangladesh Journal of Neuroscience, 2016)
Background: Acute stroke Patients are at risk of developing a wide range of complications. Among these medical complications the most common are infections, including pneumonia and urinary tract infection (UTI). This study was designed to see the frequency and risk factors of pneumonia and UTI after acute stroke in hospitalized patients. Methods : This prospective observational study was done in the Department of Neurology and Department of Medicine, Sylhet M.A.G Osmani Medical College Hospital, from May 2014 to November 2014. After hospitalization, a total number of 80 acute stroke patients were enrolled in this study. All patients of both sexes, presented with acute stroke, were confirmed by CT scan of head; vascular risk factors were recorded and relevant investigations were done. Results: Among the study subjects Urinary tract infection was found in 23 (28.8%) patients. Statistically significant risk factors for UTI were : > 65 years age (OR=2.926; 95% of CI=1.044-8.202; p=0.037). Female gender (OR=0.327; 95% of CI=0.120-0.889; p=0.026), diabetes (OR=2.015; 95% of CI=1.019-7.780; p=0.042), Severe stroke (OR=3.331; 95% of CI=1.217-9.116; p=0.017), Foley tube catheterization (OR=4.229; 95% of CI=1.492-11.982; p=0.005). Pneumonia developed in 17 (21.2%) patients and no pneumonia in 63 (78.8%) patients. Conclusion : UTI and pneumonia are common occurrence after acute stroke during stroke hospitalization. Older age, female gender, diabetes mellitus, severe stroke at presentation and urinary catheterization were found the risk factors of UTI; whereas older age, severe stroke at presentation, nasogastric tube feeding, oropharyngeal suction and difficulty in swallowing were found the risk factors of pneumonia in acute stroke. Bangladesh Journal of Neuroscience 2016; Vol. 32 (2): 74-84